2022
DOI: 10.1155/2022/9668239
|View full text |Cite
|
Sign up to set email alerts
|

MSC-Derived Extracellular Vesicle-Delivered L-PGDS Inhibit Gastric Cancer Progression by Suppressing Cancer Cell Stemness and STAT3 Phosphorylation

Abstract: Mesenchymal stem cell- (MSC-) derived extracellular vesicles (EVs) serving as delivery system have attracted extensive research interest, especially in cancer therapy. In our previous study, lipocalin-type prostaglandin D2 synthase (L-PGDS) showed inhibitory effects on gastric cancer growth. In this study, we aimed to explore whether MSC-EV-delivered L-PGDS (EVs-L-PGDS) could inhibit gastric cancer progression. EVs-L-PGDS were generated from MSCs transfected with adenovirus encoding L-PGDS. Cell colony-forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The same could be demonstrated in another study where L-PGDS served as a potential drug to inhibit the proliferation of GC cells through the PPARγ signalling pathway ( Fukuoka et al, 2015 ). You ( You et al, 2022 ) and others found that MSC-derived extracellular vesicles overexpressing L-PGDS could inhibit GC progression by regulating GC cell stemness and inhibiting STAT3 phosphorylation. This suggests that MSC-derived exosomes could be an effective vehicle for GC therapy.…”
Section: Roles Of Msc-derived Exosomes In Gi Cancersmentioning
confidence: 99%
“…The same could be demonstrated in another study where L-PGDS served as a potential drug to inhibit the proliferation of GC cells through the PPARγ signalling pathway ( Fukuoka et al, 2015 ). You ( You et al, 2022 ) and others found that MSC-derived extracellular vesicles overexpressing L-PGDS could inhibit GC progression by regulating GC cell stemness and inhibiting STAT3 phosphorylation. This suggests that MSC-derived exosomes could be an effective vehicle for GC therapy.…”
Section: Roles Of Msc-derived Exosomes In Gi Cancersmentioning
confidence: 99%
“…In addition to miRNAs, the piggybacking of endogenous proteins (enzymes [ 133 135 ], cytokines [ 136 ], and transcription factors [ 137 ]) has improved the therapeutic efficacy of MSC-exosomes in a variety of ischemic diseases. Wei et al used an adenoviral transfection system to transfect human antiprotease alpha-1 antitrypsin (hAAT) into MSCs (hAAT-MSCs) and found that hAAT-MSCs -exosomes exhibited more beneficial effects in immunoregulation [ 134 ].…”
Section: Engineering Msc-derived Exosomes For Improving Therapeutic P...mentioning
confidence: 99%
“…You et al used EVs from MSCs transfected with an adenoviral vector with a gene encoding lipocalin type prostaglandin D2 synthase (L-PGDS). EVs-L-PGDS inhibited gastric cancer growth, induced cell apoptosis, reduced the expression of stem cell markers including Oct4, Nanog, and Sox2, and inhibited STAT3 phosphorylation in SGC-7901 gastric cancer cells [ 177 ].…”
Section: Antitumor Properties Of Mesenchymal Stromal Cell Derived Ext...mentioning
confidence: 99%